Performance Analysis of Aviobridges in the Context of Improving Services and Revenue at I Gusti Ngurah Rai International Airport, Bali: Analisis Performansi Aviobridge Dalam Rangka Peningkatan Pelayanan dan Pendapatan di Bandar Udara Internasional I Gusti Ngurah Rai Bali - I Gede Ananda Mahendra Putra; Dwi Afrianto; Ika Endrawijaya (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
The rapid growth of air transportation highlights the critical importance of airport infrastructure management, especially in supporting facilities such as aviobridges. I Gusti Ngurah Rai International Airport in Bali, as Indonesia's primary tourism gateway, requires optimal facility management to enhance passenger comfort and increase airport revenue. This study aims to analyze aviobridge performance in relation to passenger service quality and its contribution to airport income. A descriptive qualitative method was applied through observation, interviews, and documentation focusing on usage frequency, maintenance conditions, and financial contribution of aviobridges. The results show a very high usage frequency with uneven distribution among units, technical disruptions affecting service quality, and maintenance schedules misaligned with flight peak hours. Besides supporting passenger convenience, aviobridges also play a strategic role in boosting airport aeronautical revenues. The findings underline the need to improve aviobridge operational management through unit rotation arrangements, maintenance schedule adjustments, and optimization of commercial functions. Effective aviobridge management has the potential to enhance service quality while sustainably increasing airport revenues.